Pesantren Academic Culture, Student Engagement and Academic Achievement: The Mediating Role of Learning Motivation - Sulaiman Abdul Rasid; M. Fadli Al Azhari; Isnanur Faizah; Levi Nur Alfiah (Al-Mudarris, 2026)
This study aims to examine the influence of pesantren culture and participation in regional student organizations on the academic achievement of Sumatran students studying in pesantren environments in Java, with learning motivation as a mediating variable. This study employed a quantitative ex-post facto design using a cross-sectional survey involving 57 students selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that organizational participation significantly influences academic achievement (β = 0.560; p = 0.002), while the pesantren environment significantly affects learning motivation (β = 0.345; p = 0.000). Academic achievement also significantly influences learning motivation (β = 0.513; p = 0.000). Furthermore, academic achievement significantly mediates the relationship between organizational participation and learning motivation (β = 0.288; p = 0.005). The findings demonstrate that pesantren function not only as educational institutions but also as transformative Islamic learning ecosystems integrating spirituality, discipline, morality, collaborative learning culture, and intellectual development. Participation in regional organizations contributes to leadership development, communication skills, teamwork, and social solidarity grounded in Islamic values. Learning motivation within pesantren culture is strengthened through Islamic educational values such as niyyah, mujahadah, and thalabul ‘ilm. This study contributes to Islamic education discourse by emphasizing that academic achievement is shaped through the integration of pesantren culture, organizational engagement, spiritual discipline, and adaptive collaborative learning experiences.